Giving of Extra Virgin Olive Oil for Hemodialysis Patients Reduce Uremic Pruritus - Hrisudani, Ni Nyoman Muni; Hrisudani, Ni Nyoman Muni; Widyawati, Ika Yuni; Hidayati, Laily (International Journal of Psychosocial Rehabilitation, 2020)
Pruritus was a grievance of most often occurs in patients with hemodialysis. Pruritus was defined as an itch which happened over 6 months regularly and around 6 months after the beginning of analyzed and usually more increased with his hemodialysis. A negative impact on patient was difficulty sleeping and a mood that also related with mortality increased. This requires proper treatment which is one of them by giving extra virgin olive oil (EVOO) on uremic pruritus. The aimed of this research was to find out the effect of giving extra virgin olive oil towards uremic pruritus to hemodialysis patient in the hemodialysis’s room Hospital Common the Province of West Nusa Tenggara. Quasy-Experimental Design was used in this research. The sampling method was using purposive sampling method. The sample of this research were 45 hemodialysis patients. They were divided into two group 25 respondents as control group and 20 respondents as treatment group. The independent variable in this research was applying extra virgin olive oil and dependent variable was uremic pruritus. Data were taken with 5-D Itch scale and analyzed using Wilcoxon signed Rank Test and Mann Whitney Test level α≤0.05. Result: Statistic analyze for the treatment group showed p=0.000, and control group showed p=0.083, while statistic analyze revealed p=0.000. EVOO could improve of uremic pruritus in hemodialysis patients. It was recommended to apply EVOO for uremic pruritus. The further research should focus on extra virgin olive oil usage with observation at home.